Karakteristik Teknis Prioritas Proses Produksi Karung Goni Plastik dengan QFD - Rahmi M Sari (Media Teknika, 2016)
Woven sacks made of plastic are used by various businesses. One of these business sectors that use plastic woven sacks is rice refining company. During this time, the quality of the resulting plastic woven products is still low and inconsistent. The Company experienced many problems with product defects caused by the production process. This is demonstrated by the large number of plastic woven sacks is not elastic, cannot withstand the load and tear. Troubleshooting for plastic woven products can be solved by QFD as a tool for identifying the need for good production process and connecting them with technical characteristics. The main focus of this method is to engage customers and experts in the product development process. Results of QFD would be used to improve product design. The results of this study indicate that the thread rolling process is a major cause of problems.